The analysis of groundwater nitrate pollution and health risk assessment in rural areas of Yantai, China - Guimei Yu; Jiu Wang; Lei Liu; Yun Li; Yi Zhang; Songsong Wang (BMC, 2020)
Abstract Background Nitrate is one of the most common chemical contaminants of groundwater, and it is an important unqualified factor of rural groundwater in Yantai. In order to assess the risk of exposure to drinking water nitrate for adults and juveniles, in recent years, we monitored the nitrate concentrations in rural drinking water,a model was also used to assess the human health risk of nitrate pollution in groundwater. Methods From the year 2015 to 2018, the drinking water in rural areas of Yantai was tested according to the "Sanitary Standard for Drinking Water" (GB5749-2006). The principal component analysis was used to analyze the relationship between groundwater chemicals and nitrate. The model was used to assess human health risks of groundwater nitrate through the drinking water and skin contact. Results A total of 2348 samples were tested during the year 2015-2018.Nitrate and total dissolved solids, total hardness, chloride are all relevant, the above indicators may come from the same source of pollution; The median nitrate content (CEXP50) was 17.8 mg / L; the risk of exposure in each group was ranked as: Juveniles > Adult female > Adult male;the median health risk (HQ50) for minors and adults exceed 1. Conclusions The concentrations of nitrate is stable and does not change over time. The high concentration of nitrate in rural areas of Yantai may be the result of the interaction of fertilizers and geological factors. The risk of exposure to nitrate in juveniles and adults is above the limit, so it is necessary to be on the alert for the high levels of nitrate.